A positive photoresist composition
By using a specific proportion of film-forming resin and diazoquinone photosensitizer in the photoresist, combined with appropriate surfactants and organic solvents, the lens defects caused by photoresist coating defects and exposure energy differences are solved, and the lens defects are improved. The product quality and consistency of the monitor.
Patent Information
- Application Number
- CN202211201671.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-09-29
AI Technical Summary
In the manufacturing process of flat panel displays, lens defects caused by photoresist coating defects and exposure energy differences seriously affect product quality, resulting in high defect rate.
A positive photoresist composition consisting of 65%-80% film forming resin, 19%-30% diazoquinone photosensitizer and 0.001%-5% surfactant, and a specific film forming resin and photosensitive agent are adopted. The proportions, combined with appropriate organic solvents, are used in the lithography process to reduce lens defects.
It effectively reduces the occurrence of lens defects in lithography process, improves the stability and consistency of pattern line width, and reduces the defective yield rate.
Smart Images

Figure CN115494696B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a photoresist composition. Background Art
[0002] In the manufacturing process of flat panel displays, various (photoresist) coating defects generated during the exposure process are one of the main reasons for reducing product quality, increasing the defect rate, and reducing the overall yield rate. The difference in coating thickness between the photoresist coating defect and the surrounding area will cause visible differences in the line width of the pattern after development. The names of various coating defects vary depending on the display manufacturer. The most commonly used terms are used in this invention for description.
[0003] The most representative coating defects produced in the manufacturing process of flat panel displays include: 1) ejector pin defects. Since the substrate used to make the display screen is glass, the temperature difference between the part with ejector pins contacting the glass and the part without ejector pins contacting the glass during baking causes a difference in film thickness, thus causing ejector pin defects; 2) cloud defects. These defects are caused by uneven volatilization of organic solvents at different positions on the surface of the glass substrate; 3) linear defects. During the slit-type glue spreading process, entrained bubbles or solid particles are generated as the slit-type glue outlet moves.
[0004] The picture quality of LCD TVs has been upgraded from high definition to 4K and 8K, and the resolution has gradually increased. This requires that more thin-film transistors need to be formed on the same size substrate in the manufacturing process of flat-panel displays. To this end, the size of the gate electrode, source / drain electrode, and pixel electrode needs to be gradually reduced. If a higher resolution is required, the line width of the gate electrode, source / drain electrode, and pixel electrode can only be gradually reduced. In large graphics, due to the narrowing of the line width of the pattern, even small critical size differences will form defects, leading to serious adverse causes. The most representative defect is the lens defect.
[0005] The lithography machines used in the production of flat panel displays are mainly Nikon and Canon brand lithography machines, of which most of the production lines above the 10th generation use Nikon lithography machines. Nikon lithography machines use a combination of multiple small lenses to achieve the exposure effect that a complete large lens can achieve. There will be slight differences in exposure energy between multiple small lenses, which will lead to regular and subtle differences in exposure patterns. This regular exposure pattern difference will affect the degree of movement of liquid crystal molecules in subsequent processes, and ultimately lead to defects visible to the naked eye in the TV screen, resulting in defective products.
[0006] The photoresist used in the manufacturing process of flat panel display screens is generally composed of phenolic resin, photosensitizer, organic solvent, surfactant and additive. Phenolic resin is a high molecular polymer formed by condensation of phenol and aldehyde (especially formaldehyde). Phenolic compounds suitable for preparing such phenolic resins include phenol, m-cresol, o-cresol, p-cresol, 2,4-xylenol, 2,5-xylenol, 3,4-xylenol and 3,5-xylenol. Diazoquinone photosensitizers are mainly used in the manufacture of flat panel displays. Such photosensitizers are formed by esterification of polyhydroxybenzophenone and its analogs with 2-diazo-1-naphthoquinone-5-sulfonic acid (5-DNQ) or 2-diazo-1-naphthoquinone-4-sulfonic acid (4-DNQ).
[0007] BP PAC 3XX type photosensitizers as shown in formula 1 and BP PAC 4XX type photosensitizers as shown in formula 2 are mainly used to manufacture large display screens such as televisions and can be used alone or in combination; TPPA PAC 3XX type photosensitizers as shown in formula 3 and THPE PAC 3XX type photosensitizers as shown in formula 4 are mainly used to manufacture small mobile high-resolution displays and can be used alone or in combination to obtain better resolution. However, using them alone requires too long an exposure time. In order to reduce the exposure time and prevent the occurrence of T-TOP patterns, they are usually mixed with BP PAC 3XX or BP PAC 4XX. Generally, BP PAC 70% and TPPA PAC or THPE PAC 30% are used in a mixed ratio.
[0008] In the above application, the amount of diazoquinone photosensitizer used is preferably 2% to 10% of the total weight of the photoresist composition to ensure that the photoresist composition has appropriate photosensitivity and resolution. The photoresist composed of phenolic resin and diazoquinone photosensitizer generally has better resolution as the content of photosensitizer increases, but the exposure time needs to be extended; on the contrary, the exposure time is shortened when the content of photosensitizer decreases, but the resolution decreases. Therefore, the content of photosensitizer in the photoresist composition used for flat panel displays generally accounts for 20% to 25% of the total weight of the solid components.
[0009]
[0010] in:
[0011] Summary of the invention
[0012] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a positive photoresist composition.
[0013] The technical solution of the present invention is summarized as follows:
[0014] A positive photoresist composition is composed of solid components and organic solvents in a mass ratio of 10-30:100, wherein the solid components are composed of 65%-80% by weight of a film-forming resin, 19%-30% by weight of a photosensitizer and 0.001%-5% by weight of a surfactant.
[0015] The film-forming resin is shown in Formula I or Formula II:
[0016]
[0017] In Formula I or Formula II, R1 is selected from H, OH, CH3, CH2OH or CH2CH2OH; R2 is selected from H, OH, CH3, CH2OH or CH2CH2OH; R3 is selected from H, OH, CH3, CH2OH or CH2CH2OH; A n The weight average molecular weight is 2000-20000; B m The weight average molecular weight is 2000-20000; C p The weight average molecular weight is 2000-20000; D b The weight average molecular weight is 2000-20000.
[0018] The photosensitizer is shown in Formula 1 to Formula 4, wherein D is shown in Formula 5 or Formula 6:
[0019]
[0020] The surfactant is Si-Type: TEGO 440 (EVONIK) or F-Type F-560 (DIC)
[0021] The organic solvent is at least one of (2-ethoxyethyl) acetate, (2-methoxyethyl) acetate, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, ethyl lactate and butyl acetate.
[0022] Advantages of the present invention: The positive photoresist composition of the present invention is applied to existing exposure equipment and photolithography processes (coating, exposure and development), which can avoid lens defects in the photolithography process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a method for preparing test pieces for testing. DETAILED DESCRIPTION
[0024] The present invention will be further described below by means of specific examples.
[0025] The film-forming resin is shown in Formula I or Formula II:
[0026]
[0027] In Formula I or Formula II, R1 is selected from H, OH, CH3, CH2OH or CH2CH2OH; R2 is selected from H, OH, CH3, CH2OH or CH2CH2OH; R3 is selected from H, OH, CH3, CH2OH or CH2CH2OH; A n The weight average molecular weight is 1000-20000; B m The weight average molecular weight is 1000-20000; C p The weight average molecular weight is 1000-20000; D b The weight average molecular weight is 1000-20000.
[0028] The photosensitizer is shown in Formula 1-Formula 4, wherein D is shown in Formula 5 or Formula 6:
[0029]
[0030] in:
[0031]
[0032] Example 1
[0033] A positive photoresist composition is composed of a solid component and an organic solvent in a mass ratio of 20:100, wherein the solid component is composed of 70% by weight of a film-forming resin, 25% by weight of a photosensitizer and 5% by weight of a surfactant.
[0034] The film-forming resin is shown in formula I;
[0035] In formula I, R1 is OH; R2 is H; R3 is CH2CH2OH;
[0036] A n The weight average molecular weight is 10000; B m The weight average molecular weight is 10000;
[0037] The photosensitizer is shown in Formula 1, wherein D is shown in Formula 5:
[0038] Surfactant is Si-Type: TEGO 440 (EVONIK)
[0039] The organic solvent was (2-ethoxyethyl) acetate.
[0040] Using the above lens defect evaluation method, the photoresist was coated, exposed and developed, and then the line width of the 3μmL / S pattern was measured using SEM, see Table 1.
[0041] Table 1
[0042] 3μm L / S pattern CD(μm) CD difference (3μm-actual CD) Comparative Example 1 2.55μm 0.45μm Comparative Example 2 2.51μm 0.49μm Example 1 2.71μm 0.29μm Example 2 2.84μm 0.16μm Example 3 2.90μm 0.10μm Example 4 2.89μm 0.11μm Example 5 2.95μm 0.05μm Example 6 2.70μm 0.3μm Example 7 2.82μm 0.18μm Example 8 2.89μm 0.11μm Example 9 2.91μm 0.08μm Example 10 2.96μm 0.04μm
[0043] This small CD (critical dimension) difference is caused by the influence of overlapping lenses in the mass production process. The present invention is very beneficial for suppressing the CD (critical dimension) difference caused by the influence of overlapping and non-overlapping lenses when manufacturing large display panels.
[0044] Example 2
[0045] A positive photoresist composition is composed of a solid component and an organic solvent in a mass ratio of 10:100, wherein the solid component is composed of 65% by weight of a film-forming resin, 30% by weight of a photosensitizer and 5% by weight of a surfactant.
[0046] The film-forming resin is shown in Formula I:
[0047] In formula I, R1 is H, R2 is OH; R3 is CH2OH; A n The weight average molecular weight is 2000; B m The weight average molecular weight is 2000.
[0048] The photosensitizer is shown in Formula 2, wherein D is shown in Formula 6:
[0049] Surfactant: F-Type F-560 (DIC)
[0050] The organic solvent was (2-methoxyethyl) acetate.
[0051] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0052] Example 3
[0053] A positive photoresist composition is characterized in that it is composed of solid components and organic solvents in a mass ratio of 30:100, wherein the solid components are composed of 80% by weight of a film-forming resin, 19.999% of a photosensitizer and 0.001% of a surfactant.
[0054] The film-forming resin is shown in Formula I:
[0055] In Formula I, R1 is CH3; R2 is CH2OH; R3 is OH; A n The weight average molecular weight is 20000; B m The weight average molecular weight is 20000;
[0056] The photosensitizer is shown in Formula 3, wherein D is shown in Formula 5:
[0057] Surfactant is Si-Type: TEGO 440 (EVONIK)
[0058] The organic solvent is propylene glycol methyl ether acetate.
[0059] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0060] Example 4
[0061] A positive photoresist composition is composed of a solid component and an organic solvent in a mass ratio of 10:100, wherein the solid component is composed of 65% by weight of a film-forming resin, 30% by weight of a photosensitizer and 5% by weight of a surfactant.
[0062] The film-forming resin is shown in Formula I:
[0063] In Formula I, R1 is CH2CH2OH, R2 is CH3; R3 is H; A n The weight average molecular weight is 5000; B m The weight average molecular weight is 5000.
[0064] The photosensitizer is shown in Formula 4, wherein D is shown in Formula 6:
[0065] Surfactant: F-Type F-560 (DIC)
[0066] The organic solvent is propylene glycol monomethyl ether.
[0067] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0068] Example 5
[0069] A positive photoresist composition is characterized in that it is composed of solid components and organic solvents in a mass ratio of 30:100, wherein the solid components are composed of 80% by weight of a film-forming resin, 19% of a photosensitizer and 1% of a surfactant.
[0070] The film-forming resin is shown in Formula I:
[0071] In Formula I, R1 is CH2OH; R2 is CH2CH2OH; R3 is CH3, and A n The weight average molecular weight is 7000; B m The weight average molecular weight is 7000;
[0072] The photosensitizer is shown in Formula 1, wherein D is shown in Formula 5:
[0073] Surfactant is Si-Type: TEGO 440 (EVONIK)
[0074] The organic solvent is a mixed solvent of ethyl lactate and butyl acetate in a volume ratio of 1:1.
[0075] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0076] Example 6
[0077] A positive photoresist composition is composed of a solid component and an organic solvent in a mass ratio of 20:100, wherein the solid component is composed of 70% by weight of a film-forming resin, 25% by weight of a photosensitizer and 5% by weight of a surfactant.
[0078] The film-forming resin is shown in Formula II:
[0079] In formula II, R1 is OH; R2 is H; R3 is CH2CH2OH;
[0080] C P The weight average molecular weight is 10000;
[0081] D b The weight average molecular weight is 10000;
[0082] The photosensitizer is shown in Formula 1, wherein D is shown in Formula 5:
[0083] Surfactant is Si-Type: TEGO 440 (EVONIK)
[0084] The organic solvent was (2-ethoxyethyl) acetate.
[0085] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0086] Example 7
[0087] A positive photoresist composition is composed of a solid component and an organic solvent in a mass ratio of 10:100, wherein the solid component is composed of 65% by weight of a film-forming resin, 30% by weight of a photosensitizer and 5% by weight of a surfactant.
[0088] The film-forming resin is shown in Formula II:
[0089] In formula II, R1 is H, R2 is OH; R3 is CH2OH;
[0090] The C P The weight average molecular weight is 2000; D b The weight average molecular weight is 2000.
[0091] The photosensitizer is shown in Formula 2, wherein D is shown in Formula 6:
[0092] Surfactant: F-Type F-560 (DIC)
[0093] The organic solvent was (2-methoxyethyl) acetate.
[0094] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0095] Example 8
[0096] A positive photoresist composition is characterized in that it is composed of solid components and organic solvents in a mass ratio of 30:100, wherein the solid components are composed of 80% by weight of a film-forming resin, 19.999% of a photosensitizer and 0.001% of a surfactant.
[0097] The film-forming resin is shown in Formula II:
[0098] In formula II, R1 is CH3; R2 is CH2OH; R3 is OH;
[0099] The C P The weight average molecular weight is 20000; D b The weight average molecular weight is 20000;
[0100] The photosensitizer is shown in Formula 3, wherein D is shown in Formula 5:
[0101] Surfactant is Si-Type: TEGO 440 (EVONIK)
[0102] The organic solvent is propylene glycol methyl ether acetate.
[0103] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0104] Example 9
[0105] A positive photoresist composition is composed of a solid component and an organic solvent in a mass ratio of 10:100, wherein the solid component is composed of 65% by weight of a film-forming resin, 30% by weight of a photosensitizer and 5% by weight of a surfactant.
[0106] The film-forming resin is shown in Formula II:
[0107] In formula II, R1 is CH2CH2OH, R2 is CH3; R3 is H;
[0108] The C P The weight average molecular weight is 5000; D b The weight average molecular weight is 5000.
[0109] The photosensitizer is shown in Formula 4, wherein D is shown in Formula 6:
[0110] Surfactant: F-Type F-560 (DIC)
[0111] The organic solvent is propylene glycol monomethyl ether.
[0112] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0113] Example 10
[0114] A positive photoresist composition is characterized in that it is composed of solid components and organic solvents in a mass ratio of 30:100, wherein the solid components are composed of 80% by weight of a film-forming resin, 19% of a photosensitizer and 1% of a surfactant.
[0115] The film-forming resin is shown in Formula II:
[0116] In formula II, R1 is CH2OH; R2 is CH2CH2OH; R3 is CH3;
[0117] The C P The weight average molecular weight is 7000; D b The weight average molecular weight is 7000;
[0118] The photosensitizer is shown in Formula 1, wherein D is shown in Formula 5:
[0119] Surfactant is Si-Type: TEGO 440 (EVONIK)
[0120] The organic solvent is a mixture of ethyl lactate and butyl acetate in a volume ratio of 1:1.
[0121] Using the above lens defect evaluation method, the positive photoresist composition was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured using SEM, see Table 1.
[0122]
[0123] Aggregation of various examples:
[0124] use (wherein R1 is selected from H, OH, CH3, CH2OH or CH2CH2OH; R2 is selected from H, OH, CH3, CH2OH or CH2CH2OH; R3 is selected from H, OH, CH3, CH2OH or CH2CH2OH) and formaldehyde to obtain a polymer, and the polymer is respectively reacted with 2-diazo-1-naphthoquinone-5-ylsulfonyl chloride (5-DNQ, ) or 2-diazo-1-naphthoquinone-4-ylsulfonyl chloride (4-DNQ, ) are condensed to prepare photosensitive polymers (film-forming resins) with structures such as Formula I or Formula II. The photosensitive polymers can form photolithographic patterns without adding other photosensitizers.
[0125] The positive photoresist composition of the present invention is in liquid form and is suitable for being deposited on a glass substrate. The surface of the glass substrate is coated with a metal film such as Cu, Mo or ITO with a thickness of about 0.05 to 0.5 μm. It has an appropriate volatilization speed and can provide a uniform and smooth coating.
[0126] In addition, a small amount of sensitizer, adhesion enhancer, etc. can be added to the positive photoresist composition formula of the present invention to obtain the best practical use effect.
[0127] Evaluation Methods for Lens Defects
[0128] In the present invention, in order to evaluate the lens defects, the prepared positive photoresist composition is uniformly coated on a 10 cm × 10 cm glass substrate, baked on a 100°C hot plate for 90 seconds, and then the glass substrate coated with the photoresist is exposed to EOP energy (first exposure) using a 3μm L / S pattern photomask, and then the EOP energy of 5%, 10%, 20%, 30%, and 50% is used for secondary exposure. Then, it is developed in a 2.38% TMAH developer for 70 seconds by drip irrigation, and then washed with ultrapure water, and the ultrapure water remaining on the glass substrate is removed by nitrogen, and finally the line width of the 3μm L / S pattern is measured by a scanning electron microscope SEM.
[0129] Comparative Example 1
[0130] 20 grams of phenolic resin with a m-cresol / p-cresol ratio of 50:50 and a weight average molecular weight of 8000 and 5 grams of purchased diazoquinone photosensitizer PAC430 were dissolved in 75 grams of propylene glycol monomethyl ether acetate solvent, and 500ppm of silicone surfactant was added to prepare a universal m- / p-cresol resin type photoresist. Using the above lens defect evaluation method, the photoresist was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured by SEM, as shown in Table 1.
[0131] Comparative Example 2
[0132] 20 grams of phenolic resin with a m-cresol / p-cresol ratio of 50:50 and a weight average molecular weight of 8000 and 5 grams of purchased diazoquinone photosensitizer PAC435 were dissolved in 75 grams of propylene glycol monomethyl ether acetate solvent, and 500ppm of silicone surfactant was added to prepare a universal m- / p-cresol resin type photoresist. Using the above lens defect evaluation method, the photoresist was coated, exposed and developed, and then the line width of the 3μm L / S pattern was measured by SEM, as shown in Table 1.
Claims
1. A positive photoresist composition, characterized in that The composition is composed of a solid component and an organic solvent in a mass ratio of 10-30:100, wherein the solid component is composed of 65%-80% by weight of a film-forming resin, 19%-30% by weight of a photosensitizer, and 0.001%-5% by weight of a surfactant; The film-forming resin is shown in Formula I or Formula II: In Formula I or Formula II, R1 is selected from H, OH, CH3, CH2OH or CH2CH2OH; R2 is selected from H, OH, CH3, CH2OH or CH2CH2OH; R3 is selected from H, OH, CH3, CH2OH or CH2CH2OH; A n The weight average molecular weight is 2000-20000; B m The weight average molecular weight is 2000-20000; C p The weight average molecular weight is 2000-20000; D b The weight average molecular weight is 2000-20000; The photosensitizer is shown in Formula 1, Formula 2, Formula 3 or Formula 4, wherein D is shown in Formula 5 or Formula 6: in:
2. A positive photoresist composition according to claim 1, characterized in that The surfactant is Si-Type: TEGO 440 or F-Type F-560.
3. A positive photoresist composition according to claim 1, characterized in that The organic solvent is at least one of (2-ethoxyethyl) acetate, (2-methoxyethyl) acetate, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, ethyl lactate and butyl acetate.